MTA versus Portland cement: review of literature - Naiana Viana Viola; Mário Tanomaru Filho; Paulo Sérgio Cerri (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: Both Mineral Trioxide Aggregate (MTA) and Portland cement (PC) have been highlighted because of their favorable biological properties, with extensive applications in Endodontics, including the possibility of using into root canal filling. Objective: This article reviews literature related to MTA and PC comparing their physical, chemical and biological properties, as well as their indications. Literature review: Literature reports studies revealing the similarities between these materials’ properties, including both biocompatibility and bone repair induction. Moreover, there is the need for the development of a root canal sealer based on these materials (MTA and PC). Conclusion: MTA and CP show promissory perspective both in Dentistry and Endodontics.